Utilization of social media marketing and E-WOM in building brand awareness at the Linggar Jati Museum - Iip Saiful Anwar; Hery Winoto Tj; Soegeng Wahyudi (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine the effect of using Social Media Marketing and E-WOM in Building Brand Awareness at the Linggarjati Museum. This study uses a qualitative approach. The subject of this research can be in the form of objects, people, and places that influence or are related to research. The information obtained about the use of social media and E-WOM to increase Linggarjati Museum's brand awareness comes from the interview process. This research was conducted from May to June 2023 which took place at the Linggarjati Museum. Data collection techniques used in the form of writing, numbers, sound, and documentation. Process Data collection instruments using three data collection techniques, including observation, open interviews, and documentation. The data analysis technique in this study used the Miles and Huberman model which consisted of three activities, namely data reduction, data display, and conclusion drawing/verification. Based on the results of the study, empirical facts were obtained in the form of: 1) Museums are one of the places or locations for implementing educational tourism activities. Museums offer visitors an experience to see and feel historical places, carry out educational activities and experience learning while traveling. 2) Efforts to optimize the media are urgently needed in order to increase awareness about the Linggarjati Museum. The provision of historical information and education is one of the main points of the existence of the Museum, but it is necessary to provide good personal and non-personal information